Magnetic diagnostic optimization for plasma equilibrium reconstruction in the HSX stellarator. (15th September 2015) - Chlechowitz, E.; Talmadge, J.N.; Hanson, J.D.; Anderson, F.S.B.; Anderson, D.T.
Abstract: A new set of 80 optimized magnetic diagnostics has been designed, built and installed in the helically symmetric experiment stellarator to enable a more accurate reconstruction of the plasma equilibrium compared to a previously installed unoptimized set. The optimization of the positions of the diagnostic coils was based on two different methods. The first technique searches for diagnostics with a high signal effectiveness. This quantity is determined by how much the variance of the reconstructed parameters, which are used to describe the equilibrium, changes depending on a change in the variance of the measurement. The results of this method are combined with a study that determines which diagnostics have the largest signal change if only a single parameter is varied. Calculations show that the new set of diagnostics reduces the uncertainty in the reconstructed plasma pressure and plasma current profile compared to the previous magnetic diagnostics and a virtual internal diagnostic set which was not optimized. With a reduction in the signal uncertainties, a further improvement can be achieved for the optimized diagnostic set, demonstrating the advantage of a careful diagnostic design process. It is shown that it is possible to design diagnostic coils which are only sensitive to either the bootstrap current or the Pfirsch–Schlüter current.